Tính tổng sau: (x ²y – 3xy ³ + 5xy) + (3x ²y + 3xy ³ – 2xy)

Question

Tính tổng sau:
(x ²y – 3xy ³ + 5xy) + (3x ²y + 3xy ³ – 2xy)

in progress 0
Kinsley 1 năm 2021-09-09T19:07:40+00:00 2 Answers 9 views 0

Answers ( )

    0
    2021-09-09T19:08:42+00:00

    `(x^2y -3xy^3 + 5xy) + ( 3x^2y + 3xy^3 – 2xy)`

    `= x^2y – 3xy^3 + 5xy+3x^2y + 3xy^3 – 2xy`

    `= (x^2y + 3x^2y) – (3xy^3 – 3xy^3) + (5xy – 2xy)`

    `= 4x^2y + 3xy`

     

    0
    2021-09-09T19:09:30+00:00

    Đáp án:

     

    Giải thích các bước giải:

    (x ²y – 3xy ³ + 5xy) + (3x ²y + 3xy ³ – 2xy)

    ⇔x ²y – 3xy ³ + 5xy + 3x ²y + 3xy ³ – 2xy

    ⇔4x ²y +3xy

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )